Acidic amelioration of soil amendments improves soil health by impacting rhizosphere microbial assemblies. (April 2022) - Chen, Dele; Wang, Xingxiang; Carrión, Víctor J.; Yin, Shan; Yue, Zhengfu; Liao, Yangwenke; Dong, Yuanhua; Li, Xiaogang
Abstract: Intensive cultivation with accompanying nitrogen fertilization leads to soil acidification in croplands of southern China, which in turn, imperils soil health, restricting the sustainability of agricultural production. Application of soil amendments is considered as a potential method for maintaining soil health; however, the underlying soil-health-promoting mechanisms are poorly understood. In the present study, we used lime, organic manure, and straw biochar, or their combinations, to treat severely acidified field plots (5 previous seasons of peanut monocropping). We analyzed the rhizosphere microbial communities, soil physicochemical properties, plant disease resistance, and plant physiological parameters at pod-bearing and pod-maturing stages of peanut. The effect of soil pH, regulated by the amendments, on the root-associated microbiome was more pronounced than the effects of other physicochemical properties. Specifically, Actinobacteria and Proteobacteria became more abundant in the rhizosphere upon the application of organic materials with lime. In vitro co-cultures of rhizosphere bacterial suspensions with a fungal pathogen revealed their enhanced disease suppression ability following treatment. Physiologically, application of organic amendments with lime promoted disease-resistance of plant roots, as determined by phenylalanine ammonia lyase and superoxide dismutase activities. The optimization of bacterial community composition in the rhizosphere played a key role in enhancing plant disease resistance, as inferred by structural equation model and network analyses. These findings suggest that the application of soil amendments reinforces disease suppression and plant physiological parameters in acidified soils by impacting microbial community assembly in the rhizosphere. Highlights: Acidic soil amelioration modified rhizosphere microbial assemblies. Rhizosphere bacterial community regulated by soil amendments enhanced suppression of fungal pathogen. Rhizosphere microbiota reprogrammed plant defense response. Manipulating rhizosphere microbial assembly in the soil microbiome–plant–pathogen system could maintain soil health.